Dual X-ray Absorbtiometry Can Predict Total and Regional Body Fat Percentage: A Comparative Study With Skinfold Thickness and Body Mass Index For Adult Women: Dual X-ray Absorbtiometry Body Fat Percentage Skinfold Thickness BMI Adult Women - Küçükkubaş, Nigar; Korkusuz, Feza (Progress in Nutrition, 2020)
Background and Purpose: Distribution and volume of total and regional fat and fat percentage is important to monitor diet and exercise in adult women. A prediction formula for adult women by examining Body Mass Index (BMI), quotas obtained from Skinfold Thickness (ST) sites and body composition compartments determined by using Dual X-ray Absorptiometry (DXA) was aimed. Participants and Method: Sixty female participants (average age 46.4 ± 3.2 years; Range 40 - 55 years) were assessed by using DXA (Lunar Model DPX) to determine body fat percentage (%BFDXA), Fat Mass (FMDXA), and Lean Body Mass (LBMDXA). Skinfold thickness sites were measured by using Skinfold Caliper (Holtain Caliper, UK). Results: A low positive correlation coefficients was found between %BF obtained from DXA and quota of suprailium ST (r=0.30 p<0.05). The highest correlation coefficient was between %BFDXA and BMI: r = 0.83 (p<0.001). Three different Regression Equations were derived to predict %BF: BMI Model %BF = 7.162 + 0.23 * BMI (R2=0.68 and SEE=2.892); Anthropometric 1, %BF = 7.346 + 0.835 * BMI + 0.169 * LEST (R2 = 0.80 and SEE = 2.341); Anthropometric 2, %BF = 8.179 + 0.714 * BMI + 0.167 * LEST + 0.114 * Chest ST (R2 = 0.80 and SEE = 2.341). Analysis of variance and confidence intervals and Bland & Altman Analysis were used to determine the validity. Intra Class Correlation (ICC) was used to determine reliability of the prediction equation. Discussion: The %BFDXA findings of the present study was 38.29 ± 5.09 and %BF by Generalized Equation was 35.69 ± 4.79, are like in underestimating those in the previous scientific studies. Anthropometry Model 1, has predictors of BMI, is more advantegous having the least ST sites (mid-thigh and medial calf) than anthropometry Model 2. Otherwise BMI model is recommended. Conclusion: BMI, LEST (sum of the medial calf and mid-thigh) and chest ST values but not other ST quotas were good predictors for prediction equations. Derived models in predicting %BF using DXA of BMI model, Anthropometric 1, Anthropometric 2 were moreover valid and reliable. While the Generalized Equation was valid, it is not reliable for the adult women population.